The Roots of Latino Urban Agency - Rosales, Rodolfo (Al Filo, Mexican American Studies Series, 2013)
The 2010 U.S. Census data showed that over the last decade the Latino population grew from 35.3 million to 50.5 million, accounting for more than half of the nation's population growth. This book collects essays that examine this phenomenal growth. In order to understand the Latino community in all its diversity, the analysis has to begin at the grassroots level. The political future of the Latino community in the United States in the twenty-first century will be largely determined by the various roles they have played in the major urban centers across the nation. These essays collectively suggest that political agency can encompass everything from voting, lobbying, networking, grassroots organizing, and mobilization, to dramatic protest. Latinos are in fact gaining access to the same political institutions that worked so hard to marginalize them.